Asthma education material for children and their families; a global survey of current resources. Issue 1 (December 2015) - Everard, Mark; Wahn, Ulrich; Dorsano, Sofia; Hossny, Elham; Le Souef, Peter
Abstract One of the keys to high quality paediatric asthma management is the provision of age appropriate information regarding the disease and its management. In order to determine whether the generation of a minimum dataset of information which can be translated into a wide range of languages might be used to assist children and their parents around the world, we undertook a survey of national Member Societies of the World Allergy Organization (WAO) to determine what educational material on asthma for children and their families already exists. A questionnaire was developed using Survey Monkey and distributed in 2014 to 263 representatives of the WAO member Societies from 95 countries. Thirty-three replies were received from thirty-one countries. The survey highlighted a considerable disparity in availability of material among the responding countries, with some countries reporting that information was freely available in hard copy and online and others reporting a lack of suitable material locally. The results highlight the need to develop a core set of simple, clear and consistent age appropriate information that can be easily translated and delivered in a cultural and educationally effective format.